Parental health and educational outcomes: The influence of parents’ health status on pupil GCSE attainment in Northern Ireland. - Miller, Sarah; Early, Erin; Dunne, Laura (International Journal of Population Data Science, 2025)
Objectives Parental physical and mental health has been shown to negatively affect children’s educational attainment; however, the extent and strength of this relationship can vary. The objective of this analysis was to explore the nature of this association using linked administrative data collected from parents and young people in Northern Ireland. Methods Using the household Census (2011), School Leavers Survey (2010-2014) and School Census (2010-2014), the analysis included n=40,003 families. This represents the first occasion in Northern Ireland where student attainment has been linked to parental health status. Maternal and paternal health status was self-reported and included: health status (5-point likert scale) and a yes/no indicator for the presence a mental health condition and/or a physical health condition. Multilevel models accounted for the hierarchical data structure and several control variables were also included in the model (wider demographic variables and the young person’s own physical and mental health status). Results The analysis showed that maternal and paternal self-reported health status (rated from very good health to very bad health) is not statistically significant in relation to pupil attainment. However, the presence of a maternal physical health condition (b=.63, SE=.21, p=.003) is significantly associated with lower pupil attainment, whilst the presence of a paternal physical health condition (b=-.31, SE=.20, p=.123) did not show a statistically significant effect. For mental health, both maternal (b=-.64, SE=.32, p=.043) and paternal mental health (b=-.77, SE=.39, p=.049) were statistically significant factors, with pupils who had one or both parents reporting poor mental health exhibiting lower attainment scores at GCSE. Conclusion This study distinguishes maternal and paternal health effects on attainment, confirming the importance of family and context. It is the first to use Northern Ireland population-wide data to analyse both parents' physical and mental health influences independently, emphasising their distinct roles in pupil success.